2020
DOI: 10.3390/app10113876
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Connectors to Enhance the Interfacial Debonding of Concrete Overlays

Abstract: Concrete bonded whitetoppings and overlays usually fail due to a loss of bond between the layers as a consequence of direct actions (traffic loads) or indirect actions (temperature differences or shrinkage in the layers). These actions generate stresses in the interface that may exceed the strength capacity of the union between layers. This paper proposed an innovative solution for this problem that consisted of placing mechanical connectors in the overlay interfaces to provide them with post-cracking strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(51 reference statements)
0
3
0
1
Order By: Relevance
“…A study (Perez et al, 2009) issued a comparison between two types of surface preparation scarification which are a kind of horizontal groove and hydro demolition is a kind of rough, in the result detected that a better bond was obtained with hydro demolition. (López-Carreño et al, 2020) experimented with the influence of mechanical connectors and concluded that screw anchor can provide adequate bond strength but better structural performance obtained with bent rebar, after two years of traffic 10 % of the slab were cracked but none of them failed at the interface. The study (Muñoz & Ángel, 2012) doesn't recommend using a grooved interface because in all experiments failure occurred at substrate except grooved surface only failure occurred at the interface.…”
Section: Surface Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A study (Perez et al, 2009) issued a comparison between two types of surface preparation scarification which are a kind of horizontal groove and hydro demolition is a kind of rough, in the result detected that a better bond was obtained with hydro demolition. (López-Carreño et al, 2020) experimented with the influence of mechanical connectors and concluded that screw anchor can provide adequate bond strength but better structural performance obtained with bent rebar, after two years of traffic 10 % of the slab were cracked but none of them failed at the interface. The study (Muñoz & Ángel, 2012) doesn't recommend using a grooved interface because in all experiments failure occurred at substrate except grooved surface only failure occurred at the interface.…”
Section: Surface Preparationmentioning
confidence: 99%
“…In order to create an equation that gives a minimum amount of error the "IBM SPSS Statistics 26" program is used with dependent and independent variables. This equation is summarized in kinds of literature (Hussein et al, 2016;López-Carreño et al, 2020;Luo, 2002;Newtson & Weldon, 2018;Sadek et al, 2019;Sritharan & Aaleti, 2017;Tayeh et al, 2012;Wibowo & Sritharan, 2018;Yang Zhang, Zhang, et al, 2020;Yang Zhang, Zhu, et al, 2020) on studies which have been performed. Equation 2 assists to understand better the flexural performance and predicting the ultimate failure load of the existing NSC structure which is planned to be strengthened with a UHPC overlay.…”
Section: Prediction Equationmentioning
confidence: 99%
“…Su dimensionamiento se hizo para resistir los esfuerzos tangenciales de las cargas de tráfico en la interfase entre los hormigones. Puede encontrarse más detalle del dimensionamiento en [6].…”
Section: -Solución Adoptadaunclassified
“…Fine grain or reactive powder concrete is a high -performance concrete with high strength, high strength and low porosity [18]. Increasing the fineness and activity of the components and removing coarse aggregates to minimize internal defects of concrete (pore space and minor cracks) are the basic principles of achieving strength and strength extremely durable [19][20][21]. Compared with conventional concrete, the fracture strength of high -performance concrete is one step higher.…”
Section: Introductionmentioning
confidence: 99%